Alluvial mining and its impact on deterioration of physical health of Malekhu Khola, Central Nepal - Khanal, Jharana (Bulletin of the Department of Geology, 2017)
The Malekhu Khola is accessible and potential for the construction materials in today’s developing phase. The study mainly concerns with mining of construction aggregate and effect of indiscriminate mining from river and its basin area which may impose many harmful effects on environment. The objective of the study is to identify the condition of river using morphological and physical parameters, and to investigate the factors which are directly responsible for the environmental degradation. Such study of rivers in present context is essential as it provides insights of strength of the river. To examine the circumstance of river, the study was proceed by selecting the area into three reaches of each 500 m, and further each reaches are divided into six transects. Both reach-scale and transect-scale attributes were assessed. The scoring was done by adding all the attributes of the standard survey sheet. A cross-sectional study was carried out along 3 different stations, Reach 1 to Reach 3 from upstream to downstream. Various fluvial parameters and data from pebble count were used to calculate morphological parameter and grain size distribution. The channel sediments were found to be extremely poorly sorted, the distribution of grain size is varied from transect to transect, which might be the result of unplanned mining. All the result acquired from field study and satellite image confirms that the river is worsening day by day. The formation of pools and deposition of organic matter show that the river is not flowing in its natural way. After all the examination, it indicates that the Malekhu Khola is being violated by the human and mining activities, thus the river reclamation measure is required at abandoned mining sites to maintain the Malekhu Khola channel morphology and habitat of the river. Bulletin of the Department of Geology, Vol. 18, 2015, pp. 59-66